Analisis Unsur Batin Puisi yang Berjudul "Negeriku" Karya Mustofa Bisri - Nurul Anisa (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
This research was motivated by the researcherâ€™s curiosity about the poetry of a K.H Mustofa Bisri which is very different from his main profession as a very famous scholar and preacher in Indonesia. Many literary works have been born from the ideas and thoughts of a K.H Mustofa Bisri. One of his literary works in the characteristic poetry of his poetry is known for its sharp and flicked language, hi often make poetry that criticizes and satirizes the socio-political and religious behaviour of the wider community. One of the poems that caught the attention of researchers was entitled â€œNegerikuâ€ through this poem he was able to express his anxiety and irritation towards the country he loved by using subtle but quite slapping language. This study aims to analyze the inner elements of poetry, namely the theme, tone, taste, and mandate of the poem entitled â€œMy Countryâ€. The method used is descriptive qualitative method. As for the results of tained with regard to reseacherâ€™s analysis, it can be concluded that in this poem 1. The theme of social justice, 2. Shows a sense of sadness, disappointment, and anxiety from a poet,3. The tone of this poem is slightly offensive or critical, and 4. The message that you want conveyed by the poet, namely optimizing human resources in Indonesia to manage the natural wealth of this country, do not want to be enslaved by the colonizers.Â Â